Administrative Reforms in Korea Articles Reprinted from the Seoul Press - Puressusha, Seuru (London Forgotten Books, 2015)
Excerpt from Administrative Reforms in Korea: Articles Reprinted From the Seoul Press The Korean Independence Agitation (seoul Press Chosen) is the title of an interesting booklet which has come to hand. Its contents are made up of a series of articles which originally appeared in the Seoul Press. The articles are particularly interesting, as throwing a somewhat new light upon the alleged stories of atrocities committed towards those Koreans who took part in the disturb auces. The view is advanced that it is unjust to think that the excesses committed by the police and others in suppressing the outbreak hadithe approval of the higher Japanese authorities. Emphasis is also given to the fact that many of the stories of atrocities committed by the Japanese were very much exaggerated by people with a strong anti-japanese bias, and that the brutality was not always on one side. There is of course a na tural tendency among many people to sympathise with the weak against the strong, but this inclination ought not to in uence our sense of justice. The booklet per forms a useful purpose by supplying what appears to be a perfectly impartial rendering of events which in the past have no doubt been distorted by prejudice and passion. Resumen tomado de https://www.bol.com/nl/f/administrative-reforms-in-korea/9200000047753838
Este libro es una reproducción de una importante obra histórica. Published by The Seoul Press office, Seoul, Chosen, Japan, Seoul, november 10, 1919.
Keywords: Korea -- Política y gobierno; Korea -- Reformas administrativas; Administrative -- reforms -- Korea